Standardization of industrial clothing production processes in the city of Pelileo, Ecuador as a factor to influence productivity - Morocho Ríos, Cristian Javier (2023)
A study was proposed in order to standardize the production processes of safety pants and shirts of a company in the city of Pelileo, Ecuador. A mixed approach was employed for the research: a situational analysis of the production process was conducted for the field study, while the product quality was assessed using a sample of 114 internal and external clients. The process was assessed using the 5M criteria (machines, labor, methods, materials and environment). The findings show that production processes did not meet the quality parameters due to a lack in quality control and insufficient infrastructure. 61 % of clients stated that quality control was lacking. 70 % of participants did not approve of the time allotted to each operator for their activities. It was concluded that it is necessary to develop a quality control procedure in order to ensure the quality of the final product.